Innovation in Group Guidance Media: E-Guide to Theraplay Based on Traditional Games for Children with Autism - Anis Tri Yuliana; Adirasa Hadi Prasetyo; Tantri Safitri; Faizatul Muflihah (Universitas PGRI Yogyakarta, 2026)
This research aims to develop innovative products in the form of group guidance media and e-guides on traditional game-based techniques for children with autism. This research uses the Research and Development (R&D) method, adopting the Borg & Gall development model, which is modified as needed. The development stage includes preliminary studies, planning, initial product manufacturing, expert testing, and product revision. Validation was conducted by two learning media experts, two counseling guidance experts, and two guidance and counseling teachers at SLB, who served as potential users. Quantitative data were collected using assessment instruments on a 1-4 scale and analyzed using the Aiken inter-rater agreement technique, while qualitative data in the form of expert input were analyzed descriptively and interpretively through triangulation. The results showed that the product received an overall validity index of 0.96 from media experts, 0.89 from BK experts, and 0.95 from potential users, all classified as